Effect of complete pellet feed on commercial goat production under the stall feeding system in Bangladesh - Ahmed, Sadek; Rakib, Md Rezaul Hai; Hemayet, Md Abu; Roy, Biplob Kumer; Jahan, Nusrat (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study aimed to identify the effect of complete pellet feed on animal performances in both on-station and on-farm trials conducted on growing goats. Materials and Methods: A complete pellet feed was developed with 40% roughage (rice straw) and 60% concentrate [rice polish (50%), maize crush (16%), soybean meal (20%), molasses (10%), salt (2%), Dicalcium Phosphate (1%), vitamin–mineral premix (0.5%), and pellet binder (0.5%)] for commercial goat production and the research trial was carried out on the research station and on the farmers’ validation level. Results: The results of the experiment on the effect of the developed complete pellet feed on goat production under stall feeding condition demonstrated that feeding complete pellet feeds helped in increasing the daily body weight gain of goats (36.96 and 52.46 gm, respectively) compared to traditional semi-intensive feeding (17.76 gm) with significantly (p < 0.05) better body condition score of goats. Feed Conversion Ratio was considerably lower (5.7) in the pellet feeding group than in the other groups where no pellet feed was used (8.32 and 8.03). Significantly (p < 0.05) lower feed price per kg weight gain was also observed in the pellet feeding group (BDT 124.22) compared to other groups (BDT 203.85 and BDT 214.74, respectively). Conclusion: The results suggest that complete pellet feed can be more economical for commercial goat production under the stall feeding condition, and farmers can be benefited by about 40% more compared to conventional grass, urea molasses straw, and concentrate-based feeding system. J. Adv. Vet. Anim. Res., 7(4): 704-709, Dec 2020 http://doi.org/10.5455/javar.2020.g471